Pickup and Delivery Problem - Pelikan, Jan; Fabry, Jan (Communications - Scientific letters of the University of Zilina, 2009)
Vehicle routing problem and traveling salesman problem are classical problems in operational research; this modification of those problems consists of a transport among nodes of the communication network using cyclical routes of vehicles with a given capacity. A transportation demand is given by the place of pickup, the place of delivery and quantity of goods. The goal is to find cyclical routes of a minimal length which ensure the transport requirements. In the paper there are two models proposed for the problem, both are demonstrated on an example. The problem is based on a case study from practice.